Survey of the modern madrasah system of education during the first half of the 20th century : a comparative study of Perak and Pattani - Khalizah Hanim Yazid (Kuliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
In the early 20th century, a modern madrasah system of education replaced the pondok system which had been growing in the Malay world since the emergence of early Malay kingdoms in the 16th century. The aim of this study is to examine why such a change from a pondok system to a modern madrasah system took place, and to compare the progress of the modern madrasah system of education in the Malay states specifically of Perak and Pattani during the first half of the 20th century. These two states were chosen because of their close proximity to one another, and also because they share the closest resemblance in socio-cultural background as Malay-Muslim societies. In tracing the development of one system into the other, several contributory factors will be examined. They include the socio-economy and politics of the local Malay-Muslim communities, their attitudes towards the modern madrasah institution, the role of the local rulers and ʻulamāʼ in developing the institution, and subsequently Western colonial powers and their attempts to protect their interests in the region i.e. Southeast Asia. In conducting this study, the researcher has employed methods of library research and content analysis, scrutinizing both relevant primary and secondary sources. Finally, as the study will show, though the people of both Malay states of Perak and Pattani had the experience of implementing the modern madrasah system of education, the progress of the system in the states varied due to several reasons that are worthy of attention.